Intracerebral transplantation for neurological disorders. Lessons from developmental, experimental, and clinical studies - Benchoua, Alexandra; Onteniente, Brigitte (Frontiers in Cellular Neuroscience, 2012)
The use of human pluripotent stem cells for cell therapy faces a number of challenges that are progressively answered by results from clinical trials and experimental research. Among these is the control of differentiation before transplantation and the prediction of cell fate after administration into the human body, two aspects that condition both the safety and efficacy of the approach. For neurological disorders, this includes two steps: firstly, the identification of the optimal maturation stage for transplantation along the continuum that transforms pluripotent stem cells into fully differentiated neural cell types, together with the derivation of robust protocols for large-scale production of end-products, and, secondly, the understanding of environmental cues that will allow maintenance of commitment and avoid the development of adverse structures. This review will summarize our knowledge on developmental processes that have been applied to achieve robust in vitro differentiation of pluripotent stem cells into neural progenitors, and will examine the effects of the recipient brain environment on the pre-transplantation commitment.